Analysis of Arabic Language Learners' Motivation and Attitudes: an AMTB Study on Final-Semester Students at STAI As-sunnah Deli Serdang - Riyadi, Slamet; Rozaanah , Rozaanah (Jurnal Al-Fawa'id : Jurnal Agama dan Bahasa, 2025)
Motivation and attitudes in Arabic language learning are critical factors in determining student success, especially for final-year students preparing to become professional Arabic teachers. This study examines these factors using Gardner's Attitude/Motivation Test Battery (AMTB) framework in the unique context of the boarding system at STAI As-sunnah Deli Serdang, Indonesia. A sequential explanatory mixed-methods design was employed, combining a quantitative AMTB survey (n=120 students, 66.67% of the population) with in-depth qualitative interviews (n=12). Results revealed high levels of both instrumental motivation (M=4.5, SD=0.55) and integrative motivation (M=4.17, SD=0.68). Religious factors emerged as the strongest influence on instrumental motivation (M=4.7, SD=0.48). Key findings revealed the significant role of the boarding system in shaping positive learning attitudes (M=4.2, SD=0.68) through consistent Arabic language exposure and intensive peer interactions. Factor analysis identified five key influences: boarding environment (0.856), teacher quality (0.789), learning facilities (0.745), peer support (0.723), and curriculum (0.698). The implications of this research emphasize the importance of fostering immersive language environments and leveraging religious contexts in developing positive motivation and attitudes in Arabic language learning. The findings are particularly relevant for Islamic higher education institutions preparing prospective Arabic teachers, providing empirical evidence of the boarding system's effectiveness in enhancing students' Arabic competency. The results extend the application of the AMTB framework in Islamic higher education contexts and offer valuable insights for designing more effective Arabic language learning programs.